Epidemiology and Outcomes of Maxillofacial Injuries in NCAA Division I Athletes Participating in 13 Sports. Issue 3 (23rd March 2022) - Mertz, Kevin C.; Bolia, Ioanna K.; English, Margaret G.; Cho, Austin W.; Trasolini, Nicholas; Hasan, Laith K.; Haratian, Aryan; Diaz, Paul; Romano, Russ; Gamradt, Seth C.; Weber, Alexander E.
Background: Maxillofacial injuries account for an estimated 11% of National Collegiate Athletic Association (NCAA) sport-related injuries and occur at a rate of 0.2-1.5 injuries per 1000 athletic events/exposures. Purpose: The purpose of this study was to report the epidemiology, treatment, and outcomes of maxillofacial injuries in NCAA Division I athletes participating in 13 sports. It was hypothesized that the rate of maxillofacial injuries would be greater than previously reported in national registry studies. Study Design: Descriptive epidemiology study. Methods: A single-institution registry was utilized to retrieve the maxillofacial injuries and surgical procedures recorded over 4 athletic seasons, for the years 2015 through 2019, across 13 NCAA Division I sports. The incidence of injuries per sport was reported as the number per 1000 athlete-exposure (AE) hours. The time lost from participation and time to complete injury resolution per sport were reported as the mean and range. Results: A total of 193 maxillofacial injuries occurred over 4 seasons. The overall incidence of maxillofacial injuries was 2.06 injuries per 1000 AE hours. The injury incidence for male and female athletes was 1.92 and 2.43 injuries per 1000 AE hours, respectively. Men's basketball (8.30 injuries per 1000 AE hours) and men's water polo (8.15 injuries per 1000 AE hours) had the highest rates of all sports. Overall, 20 athletes (10.4%) required surgery. The mean time to resolution across all sports was 33.3 days (range, 0-336 days) per injury. The mean time lost across all sports was 17.1 days (range, 0-336 days) per injury. Conclusion: At a single NCAA Division I institution, maxillofacial injuries occurred at a higher rate than previously thought and could lead to significant time lost from sport participation. Basketball players were at the highest risk of this injury. Across all sports, male athletes took longer to return to sport after a maxillofacial injury compared to female athletes, but the latter required more time to fully recover. Maxillofacial injuries may require surgical treatment, and their prevention is critical.